The semiotics of the visual image of women in the discourse of empowerment, Saudi Arabia Kingdom as a model (Al-Academy, 2022)
We studied, in this paper, the semiotics of the visual image of women in the discourse of empowerment, through three models of advertising images expressing the particularities of the Saudi Arabian environment.We aim to know how the mark operates and how it is interpreted, as a semantic process in which the meaning ranges from description to interpretation, and we studied two hypotheses:-The advertising image is a structure in which the mark corresponds to the reality and the discourse to the context.-The significance is not found in the visual sign or in the textual sign of the advertising image, but in the creative event that opens up to the social, cultural, and psychological context, and creates a field of dialogue between the image and its recipient.We approached the foundational dimensions of the communicative system in the advertising discourse by studying the levels of meaning in three models of images indicating women's empowerment.